Molecular modeling of non-canonical intramolecular RNA triple helix structures predicted from TRIPinRNA and their in vitro biophysical structure validation - Rakheja, Isha; Panda, Gayatri; Maiti, Souvik; Ray, Arjun (Journal of Physical Chemistry B, 2025)
RNA triple helices have traditionally been characterized by pyrimidine-type UA-U or CG-C triplets, with other base triplets considered to be destabilizing. However, the presence of non-canonical triplets in riboswitches and self-splicing introns suggests that triplexes containing longer stretches of such triplets may exist in the human genome too. Using molecular modeling, we investigated a chimeric triple helix derived from the FLRT2-AS1 lncRNA, confirming its stability over a 500 ns simulation. Biophysical analyses further support the formation of this triplex in vitro. Although these non-canonical structures exhibit less thermal stability compared to traditional UA-U triplets found in lncRNAs like metastasis associated lung adenocarcinoma transcript 1 and NEAT1, they may serve distinct biological functions, suggesting a dynamic and more temporal role in cellular processes. The triplex selected for this study is found in a human long non-coding RNA gene, paving the way for investigating the intriguing roles of these triple helices in cell biology.